2017
DOI: 10.1371/journal.pone.0171296
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal stabilization splint for patients with temporomandibular disorders: Meta-analysis of short and long term effects

Abstract: BackgroundPsychological discomfort, physical disability and functional limitations of the orofacial system have a major impact on everyday life of patients with temporomandibular disorders (TMDs). In this study we sought to determine short and long term effects of stabilization splint (SS) in treatment of TMDs, and to identify factors influencing its efficacy.MethodsMEDLINE, Web of Science and EMBASE were searched for randomized controlled trials (RCTs) comparing SS to: non-occluding splint, occlusal oral appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 54 publications
4
84
0
2
Order By: Relevance
“…In the case of the latter, it would be expected that relief would be given in the short term, but that it would abate significantly after 3 months. This is supported by the results of a meta-analysis by Kuzmanovoc Pficer et al [3]. The authors show that the positive short-term effects (up to 3 months) of splints are significant, whereas these effects did not persist on the long-term when compared to presently accessible data about control groups.…”
Section: Introductionmentioning
confidence: 65%
“…In the case of the latter, it would be expected that relief would be given in the short term, but that it would abate significantly after 3 months. This is supported by the results of a meta-analysis by Kuzmanovoc Pficer et al [3]. The authors show that the positive short-term effects (up to 3 months) of splints are significant, whereas these effects did not persist on the long-term when compared to presently accessible data about control groups.…”
Section: Introductionmentioning
confidence: 65%
“…Our present results demonstrate that proper distraction and stretch loading exhibit proliferation‐promoting effects on chondrocytes. These observations provide a good explanation for the effectiveness of the bite plate for TMJ OA (Kuzmanovic Pficer et al, ) and distraction treatment for knee OA (Intema, Roermund, et al, ; Intema, Thomas, et al, ; Wiegant et al, ). On the basis of the gradual growth of rodent incisors, an interruption in incisor eruption leads to an increase in occlusion.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, some clinical studies have shown that distraction improved functional abilities and decreased pain in the knee and ankle joints with OA diagnosis and improved the structure of the cartilage as well as the subchondral bone, which was presented as an increased cartilage thickness and a decreased area of denuded bone (Intema, Roermund, et al, ; Intema, Thomas, et al, ; Wiegant et al, ). Occlusal splints have been widely used in the treatment of temporomandibular disorder syndrome (TMD) (Kuzmanovic Pficer et al, ), of which OA is the end‐stage outcome. Animal experiments have indicated that raising the occlusion height in the molar region by installing dental appliances increased cartilage thickness and promoted chondrocyte proliferation in TMJs (Akagawa, Nikai, & Tsuru, ; Li, Zhang, Wu, & Qiao, ).…”
Section: Introductionmentioning
confidence: 99%
“…The most common complications refer to intrusion of the teeth covered by the splint or in contact with it, and the extrusion of the teeth not touching the appliance. For preventing those complications, the practitioner should consider indicating the patient either a full arch permissive splint, or dual splint covering both arches, during nighttime [25,26]. There is also some evidence suggesting that anterior midpoint contact permissive splints might increase the risk of further disk displacement [10].…”
Section: What Would Be the Limitations Of Splint Therapy?mentioning
confidence: 99%